Trichoderma atroviride as a biocontrol agent of Fusarium head blight by reducing the inoculum of the pathogen in wheat straw - Cabrera, Monica; Garmendia, Gabriela; Rufo, Caterina; Pereyra, Silvia; Vero, Silvana (REVISTA TERRA LATINOAMERICANA, 2020)
Fusarium head blight (FHB) is the principal disease affecting wheat worldwide, decreasing grain quality, and production. This disease is mainly caused by members of the Fusarium graminearum species complex (FGSC), which have the capability to produce mycotoxins in the contaminated grains. The pathogen overwinters on crop residues (wheat straw). Under adequate climate conditions, the pathogen conidia or ascospores infect wheat flowers, which are the susceptible part of the plant. To minimize disease incidence, cultural practices and fungicide treatments are recommended, but none of them are effective by themselves. In that sense, biological control appears to be an alternative strategy. Therefore, the aim of this study was to isolate and select native Trichoderma spp. strains for FHB control in wheat. Sixteen isolates were identif ied at species level. All of them showed at least one characteristic that could be associated to their potential ability as biological control agents. An isolate identif ied as T. atroviride was selected according to its ability to inhibit F. graminearum perithecium development on wheat straw and produce enzymes associated to wheat straw degradation, which is the pathogen physical support.